Evaluation of The Efficiency of Immunization Services at A Primary Health Care Centre of a Squatter Settlement in Karachi Research work was done at Ziauddin University, Karachi - SUMAIR ANWAR, JAMAL ABDUL NASIR, NAVEED YOUSUF, TAHSEEN KAZMI (Journal of Fatima Jinnah Medical University, 2018)
Background: According to the WHO and UNICEF only 73% of the target children in Pakistan receive all antigens up to the third dose of Diphtheria-Tetanus-Pertussis vaccine and the vaccine wastage rate is estimated to be 50% around the world as reported by World Health Organization. The objective of this study was to find out the efficiency of Expanded Programme on Immunization programme at the primary health care level at a health centre run by a private university in a squatter settlement. Methods: This cross-sectional survey was conducted from April to June 2008. The vaccination data used in the study was obtained through record documents for the period of January 2007 to June 2008 and interviews from the staff of the center. Estimated dropout rates and efficient use of vaccine vials were the main outcome variables. Results: The estimated dropout rate for Measles vaccine was 38.8%. The vaccine wastage rates were calculated using vaccine usage records from the period of January 2007 till June 2008. The wastage rates were the highest for Bacillus Calmette Guérin vaccine (35.9%) followed by Measles vaccine (29.4%) and the lowest for Diphtheria-Tetanus-Pertussis and Hepatitis B vaccines (3.9%). Conclusion: Our study concludes that the wastage rates of BCG and Measles are much higher than other vaccines. The record of vaccine wastage rate and its reasons are not properly documented at the PHC centre.